Eustachian valve endocarditis due to Pasturella multocida – A novel case - Ghanem, Hebah; Martin, Christopher; Farrer, William; Sivasubramanian, Geetha (Clinical infection in practice, 2021)
•Eustachian valve is an embryonic remnant of sinus venosus that may persist in the right atrium in some adults.•Endocarditis of the Eustachian valve is very rare.•Pasturella multocida infections are acquired most commonly from cat or dog bites.•Endocarditis due to Pasturella is rare and can happen in immunocompromised hosts.•We highlight an exceedingly rare association of Eustachian valve endocarditis caused by Pasturella multocida. The eustachian valve is an uncommon embryologic remnant of the sinus venosus present in the right atrium that may persist in some adults. Typically, in adults, right sided valvular endocarditis is associated with intravenous drug use or presence of central venous of hemodialysis catheters. Eustachian valve endocarditis is a rare cause of right sided endocarditis with very few cases reported. A routine transthoracic echocardiogram (TTE) may not be sensitive and miss this infection. Pasteurella multocida is gram negative microorganism that can rarely cause infective endocarditis. We present what we believe to be the first reported case of Eustachian valve endocarditis (EVE) caused by P. multocida.